An interventional study on the effectiveness of peer assistance for medication adherence among hypertensive patients in Purwokerto - Hening Pratiwi; Laksmi Maharani; Ika Mustikaningtias; Eling Bunga Nurani (Universitas Ahmad Dahlan, 2019)
Hypertension is a disorder of the blood vessels that hampers the transport of supply of oxygen and nutrients to the body’s tissues. Antihypertensive therapy lasts a lifetime and, so, the success of hypertension treatment strongly depends on the willingness of patients to take antihypertensives regularly. Since medical non-compliance can adversely affect the patient's health, medication supervision or peer assistance has been proposed as a way to monitor and remind hypertensive patients to adhere to prescribed daily dosage. This study aimed to determine the effect of peer assistance on adherence to hypertensive medication. It employed a quasi-experimental model with a one-group pretest-posttest design and a peer-based mentoring to achieve drug compliance as the intervention. The research samples were patients registered in the Chronic Disease Management Program (Program Pengelolaan Penyakit Kronis) at two primary health services in Purwokerto. In the first four weeks, a total of 29 respondents acted as the control group without receiving any intervention, and in the second four weeks, they became the intervention group who received peer assistance for their regular drug intake. To measure compliance, the Hill-Bone questionnaire was used. The expected maximum compliance score is 56. The results showed that the average score of compliance increased from 47.69 in the pre-control period to 49 in post-control/pre-intervention and then to 49.93 in post-intervention. The compliances during the control and intervention period had similarly significant differences with p values of 0.008 and 0.039, respectively. In conclusion, peer assistance does not affect patients’ adherence to hypertension treatment.